ANALISIS PEMETAAN KENYAMANAN JALAN BERDASARKAN INTERNATIONAL ROUGHNESS INDEX (IRI) UNTUK KENDARAAN RODA EMPAT KECAMATAN TEMBALANG, KOTA SEMARANG - Pangesti, Rendy Dwi; Kusumastuti, Dianita Ratna; Rahmawati, Roselina; Abdillah, Rifqi Aulia (Politeknik Negeri Semarang, 2024)
Assessment using the International Roughness Index (IRI) is an important indicator in evaluating the quality of road surfaces, which affects the comfort and safety of users. This study aims to map road conditions in Tembalang District, Semarang City, using the IRI value as a reference for determining maintenance budget needs. IRI data was collected using the RoadLabPro application on a smartphone installed in a four-wheeled vehicle, with measurements taken on various roads in Tembalang District to obtain a representation of overall road conditions. The collected data were analyzed using Microsoft Excel to classify road conditions into categories of Good (IRI ≤ 4.0), Moderate (4.1 ≤ IRI ≤ 8.0), Lightly Damaged (8.1 ≤ IRI ≤ 12), and Severely Damaged (IRI ≥ 12). The analysis results show that 80.65% of the road sections are in good condition, with an average IRI of 2.98 m/km, while the other 19.35% are in moderate condition with an average IRI of 4.32 m/km. Mapping data using QGIS facilitates the identification of areas that require further maintenance. The results of this study are expected to support more appropriate decision-making regarding road maintenance planning and budgeting in Tembalang District.